Motivation to learn online: analysis of the relation between expectancy, value and social support in Malaysian higher education / Nor Aziyatul Izni, ... [et al.] - Izni, Nor Aziyatul; Aksah, Saufianim Jana; Mohd Aslam, Siti Nor Aini; Alshekhly, Mohammed Abdulrazaq (Universiti Teknologi Mara Cawangan Pulau Pinang, 2024)
The rapid growth of online learning in higher learning institutions has necessitated an in-depth understanding of the factors that drive learners' motivation to engage in online educational activities. This study investigates the relationship between expectancy, value, and social support as determinants of motivation to learn online in higher learning institutions in Malaysia. Drawing upon the Expectancy-Value Theory and the importance of social support in online environments, this research aims to contribute to the existing body of knowledge by examining the interplay between expectancy, value, and social support in shaping learners' motivation to learn online. The study employs a quantitative research design, collecting data through surveys adapted from a previous study by Fowler (2018). A sample of 208 learners enrolled in various higher learning institutions in Malaysia was collected and analyzed. The study consisted of seven sections comprising relevant questions to assess the three factors influencing learning motivation. Overall, the findings indicate a significant correlation between expectancy, value, and social support in relation to learning motivation